PERANAN KELUARGA DALAM MEMBENTUK KEDISIPLINAN ANAK KELAS VII DI SMP NEGERI 1 KOTO XI TARUSAN KABUPATEN PESISIR SELATAN - Joni Adison; Suryadi Suryadi (Jurnal Inovasi Penelitian, 2020)
This research is motivated by the role of families who have not been able to shape children's discipline, such as children who are not allowed to wear socks to school and allow children to come late to school. This study aims to describe: 1) The role of the family as a protector of family members. 2) The role of the family as the socio-economic family. 3) The role of the family in fostering the basis for the principles of social life. 4) The role of the family as an initial socialization process. This type of research is quantitative descriptive. The population in this study were 199 class VII students. The sample was taken using simple random sampling technique with a total of 67 students. The instrument used was a questionnaire which was analyzed by using the percentage technique. The results of the research on the role of the family in forming children's discipline revealed that: 1) The role of the family as a protector of family members was in the very good category with a percentage of 45.45% 2) The role of the family as the socio-economic family was in the very good category with a percentage of 46.97 % 3) The role of the family in fostering the basics for the principles of social life is in the very good category with a percentage of 72.73% 4) The role of the family as the initial socialization process is in the very good category with a percentage of 74.24%. From the research findings, it is recommended that families be able to maintain the family's role in shaping children's discipline